Estudo da metodologia para estimar a geração de energia elétrica em sistemas fotovoltaicos - Landim, Italo Heyne Leite Mendonça (2020)
There is an increase in the consumption of electricity in Brazil due to the population growth associated with economic development, therefore, it is necessary to increase the supply of electricity by emphasizing renewable and clean forms in order to reduce aggression to the environment, but continue the development of the country, contributing to the production of energy through hydroelectric dams, since these have become insufficient with the scarcity of water that plagues part of the national territory. This work aims to present a way to simulate the generation of energy by photovoltaic panels, using solarimetric data, in addition to performing a comparison between the energy generated by a real system and the values obtained in the simulation. In such a way that this study can be used to better adapt the panels to the demand that is emerging in the country, allowing to compare and analyze the generation, efficiency and losses caused according to the orientation conditions and installation inclination of the photovoltaic systems. The simulations were carried out in Matlab.